Character Education Innovation in Forming Millennial Generation Personality - Arif, Mohammad (Didaktika Religia, 2022)
The education system is part of the aspired life order, which in essence cannot be separated from the connection with the teachings of Islam itself. The new Islamic education system is considered Islamic, only if it is in harmony with the concepts of the Qur’an and hadith which are the basis and purpose of Muslim life. The presence of individuals who have moral integrity is the basis for the construction of a civilized society. Moral integrity arises if individuals can make decisions through the process of correct rational consideration, and wisely implement them, following the context of a particular space and time. Moral integrity includes the ability of individuals to make practical policies that are meaningful to their own lives and others. The difference is human nature. Appreciating differences is a fundamental attitude that must be cultivated in individuals. Especially in the life of nation and state in the Unitary Republic of Indonesia, respect for differences must be cultivated in each individual, because our country stands. After all, the founders of this nation respect difference, and in that difference, they want to unite strength and energy in building the nation. Appreciating differences or tolerance is part of the character of the Indonesian people, who love the sovereignty, unity, and unity of the Republic of Indonesia.